Implementation of virtual music therapy in the practice of Czech music therapists: a best practice implementation project - Kantor, Jiří; Neuwirthová, Anna; Hořejší, Barbora; Koucun, Jan; Kantorová, Lucia; Vrbová, Tereza; Munn, Zachary; Klugarová, Jitka; Klugar, Miloslav (JBI evidence implementation, 2023)
INTRODUCTION AND AIMS: Czech music therapists lacked the skills and knowledge to adapt their practice to virtual music therapy (VMT) at the beginning of the COVID-19 pandemic, when physical contact was restricted. The aims of this project were to implement the best evidence-based recommendations concerning VMT in the practice of Czech music therapists and increase the number of therapists using VMT. METHODS: The project used the JBI Evidence Implementation Framework to promote change in the practice of participants. A baseline audit of 26 practitioners was conducted using questionnaires and interviews. The audit criteria consisted of 8 best practice recommendations, followed by the implementation of targeted strategies and a follow-up audit. RESULTS: Of the 26 music therapists, 18 began practicing VMT following the rollout of the implementation strategies. Strategies included educational workshops, instructional materials, technological support, individual counseling, and interactive training sessions. There was an increase in compliance with all audit criteria. The most critical barriers were lack of knowledge about VMT and lack of technical skills; lack of resources; technological challenges; low confidence of music therapists to provide VMT; and reduced need for VMT after the lockdown restrictions were relaxed. CONCLUSIONS: The implementation project helped to overcome temporary pandemic restrictions, increase the quality of VMT practice, develop strategies for VMT training, and identify reasons for using VMT during the pandemic and beyond.
Keywords: lékařská praxe založená na důkazech; Music Therapy; pandemie; Česká republika; lidé; muzikoterapie; Evidence-Based Practice; Czech Republic; Music; Pandemics; hudba; Humans